Kreativitas Dosen dalam Meningkatkan Minat Belajar Bahasa Arab Mahasiswa di IAIN Surakarta - Amatullah Faaizatul Maghfirah (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This study aims to know lecturer’s creativity in Arabic learning, in order to increase the student’s interest to learn Arabic. Based on the qualitative approach, the result shows that some the creativities which are able to increase student’s interest in Arabic learning such as, innovate in its methods, media, resources, and its technical evaluation. Practically, can be done through inviting native speaker, or visiting to the famous institutions that the community having fluent spoken in Arabic. In addition, warm attitude and respect to each student, would be able to motivate students to improve his/her abilities. Thereby students will have eager to always do their best in the learning process. In addition, reward would also be able to give student’s interest and motivation in their learning process. Keywords:Creativity-lecturer, Interest to learn, Arabic-language.